Efektivitas Konseling Rational Emotive Behavior Therapy (REBT) untuk Mereduksi Narcissistic Personality Disorder - Wardani, Silvia Yula; Trisnani, Rischa Pramudia (Universitas Mathla'ul Anwar Banten, 2022)
EFFECTIVENESS OF RATIONAL EMOTIVE BEHAVIOR THERAPY COUNSELING TO REDUCE NARCISSISTIC PERSONALITY DISORDER. This study aims to determine the effectiveness of rational counseling emotional behavior therapy to reduce narcissistic personality disorder. This research method is an experiment with the One Group Pretest-Posttest Design method. The subjects of this study were students of SMA Negeri 4 Madiun who had a high level of narcissistic personality disorder. The sampling technique used in this research is purposive sampling, namely the selection of research samples based on the research objectives. The research instrument used is a questionnaire. The data analysis technique used a different test or t test. The results showed that the Sign 2 tailed value was 0.000 so it could be said as an effective counseling service for Rational Emotive Behavior Therapy to reduce narcissistic personality disorder.